Tensile bond strength of dentin adhesives on acid- and laser-etched dentin surfaces - (:unkn) unknown (QUINTESSENCE PUBLISHING CO INC, 2009)
Objective: To evaluate tensile bond strengths of 2 dentin bonding agents containing solvents on Nd:YAG and Er,Cr:YSGG laser-etched dentin surface. Method and Materials: Occlusal enamel of 146 molars was removed, and exposed surfaces were ground with a diamond bur to produce bur-cut dentin surfaces. Of those teeth, 120 were assigned to 3 groups of 40 samples in which dentin was conditioned with Er,Cr:YSGG laser, Nd:YAG laser, and 37% orthophosphoric acid (control). Each group was further divided into 2 subgroups, acetone- and ethanol-containing bonding agents, and 4-mm-long x 4-mm-wide composite rods were bonded to all specimens using a Plexiglas mold. Tensile bond strength testing of 120 samples was performed at a crosshead speed of 0.5 mm/min using a 50-kgf load cell. The remaining 26 samples were examined under SEM to evaluate the adaptation/penetration of the bonding materials and the alterations in mineral content. Data were analyzed using 1-way ANOVA and Kruskal-Wallis tests; P < .05 was considered statistically significant. Results: The difference between the mean tensile bond strength values obtained with bonding agents was statistically significant in the control group. The bond strength values of the acetone-containing agent in this group were found to be higher than the ethanol-containing agent (P < .001). When compared with Nd:YAG laser, bond strength values obtained with Er,Cr:YSGG laser were higher (P < .001). The bond strength values obtained in the acid-etched group were highest for both bonding agents and demonstrated statistical significance (P < .001). Conclusion: Although in this study laser etching is more influential than the solvent type on bond strengths of dentin bonding agents, it cannot be considered as an alternative to conventional acid etching. (Quintessence Int 2009;40:865-874)
Keywords: acid etching; adhesives; dentin; Er,Cr:YSGG laser; Nd:YAG laser; tensile bond strength; ER-YAG-LASER; ND-YAG; HUMAN ENAMEL; IN-VITRO; CAVITY PREPARATION; PREPARED DENTIN; TREATED DENTIN; YSGG LASER; SYSTEMS; ER,CR-YSGG